2014 11th International Conference on Wearable and Implantable Body Sensor Networks 2014
DOI: 10.1109/bsn.2014.23
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Day-Long Recording Stability and Muscle Force Prediction between BSN-Based Mechanomyography and Electromyography

Abstract: Day-long continuous monitoring requires stable sensors that can minimise the effects of drift and maintain high accuracy and precision over time. We have recently shown that our inertial motion tracking system can capture stable kinematic data, calibrated against ground-truth over a long period of time. However, for many clinical and daily life activities, it is also essential to monitor the muscle-activity. In this study, we evaluate the long-term recording stability of our prototype mechanomyography (MMG) se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…We evaluated our wink-based system against two other approaches: Myo armband EMG gesture triggers and voice based command which are alternative modalities to control an assistive glove. However we note that the suitability for EMG in day-long use has skin-contact based limitations [27], as well as electrical noise and humidity of the environment.…”
Section: Discussionmentioning
confidence: 95%
“…We evaluated our wink-based system against two other approaches: Myo armband EMG gesture triggers and voice based command which are alternative modalities to control an assistive glove. However we note that the suitability for EMG in day-long use has skin-contact based limitations [27], as well as electrical noise and humidity of the environment.…”
Section: Discussionmentioning
confidence: 95%
“…The addition of temporal structure has a direct application to prosthetic control: We previously showed that learning the likelihood of future movement sequences in natural behaviour allows to better decode movement intention by combining the estimate from the measurements on the body (e.g. EMG or MMG [19], [20]) with the known temporal structure of the behaviour [21], [22].…”
Section: Discussionmentioning
confidence: 99%
“…approach to neurotechnology [33]- [36], where we rely on smart software and understanding of the underlying neurological challenge, instead on investing in expensive high-fidelity hardware. Beyond heart diagnostics related applications of this technology, our approach could be also integrated in our ETHO1 wireless kinematic body sensor network [37]- [39] using the accelerometer sensor of a single node when strapped on the chest of a subject. This will enable us to pursue large scale field studies with patient and control groups at an affordable price while recording a wider range of human behaviour modalities (heart activity, motor movement kinematics and neurological signals) in unconstrained, daily-life environments.…”
Section: Discussionmentioning
confidence: 99%